Analysis of Product Costs Using the Full Costing Method and Determining Selling Prices at CV Artha Jaya - Farid Al Farizi; Rheinhat Surya Negara; Mochamad Reza Adiyanto (Indonesian Journal of Economic & Management Sciences, 2023)
The aim of this research is to assess the process of determining product cost prices and selling prices at CV Artha Jaya. The results of this research indicate that there are deficiencies in the company's calculation of the product cost, with it being known that the company's product cost price for Prentol roof tiles is IDR. 2,200, mantili roof tiles Rp. 2,100, trihek paving Rp. 1,300, and hexagon paving Rp. 1,200. However, after evaluation, the basic product price for Prentol roof tiles became Rp. 2,299, mantili roof tiles Rp. 2,125, trihek paving Rp. 1,343, and hexagon paving Rp. 1,581. This inaccuracy occurred because the company did not include a number of production costs in calculating the cost price, including depreciation costs for factory buildings, as well as depreciation costs for machinery and equipment